TRANSFIGURED LEADERSHIP: KEPEMIMPINAN ALKITABIAH SEBAGAI FONDASI MITIGASI RISIKO DIGITAL - Wahju Astjarjo Rini; Andreas Fernando; Carolina Etnasari Anjaya (Manna Rafflesia, 2024)
In an increasingly digital era, Christian leaders face new challenges in managing digital risks. To face these challenges, Christian leadership needs to be based on the spiritual values ​​contained in the event of Christ's transfiguration. This article explores the meaning of Christ's transfiguration and its implications for contemporary Christian leadership. The concept of "Transfigured Leadership" can be a valuable approach for Christian leaders to face these challenges from the perspective of Christian spirituality. The method used is a descriptive qualitative analysis of the Bible and literature with related themes. The research results show that the transfiguration of Christ reveals the character of Christ as a sanctified Messiah, a leader whose life is pleasing to the Father, and a role model for His followers. Christian leadership values ​​that originate from the transfiguration of Christ require leaders who live in holiness, have a close relationship with God, humility, willingness to make sacrifices, obedience to their calling, and continuous self-transformation. By focusing on the example of Christ's leadership, Christian leaders are expected to implement leadership that is oriented toward spiritual transformation.